Cell proliferation of human bone marrow mesenchymal stem cells on biodegradable microcarriers enhances in vitro differentiation potential - Sun, L.‐Y. (Cell Prolif, 2010)
Objectives:  For reasons of provision of highly‐specific surface area and three‐dimensional culture, microcarrier culture (MC) has garnered great interest for its potential to expand anchorage‐dependent stem cells. This study utilizes MC for in vitro expansion of human bone marrow mesenchymal stem cells (BMMSCs) and analyses its effects on BMMSC proliferation and differentiation. Materials and methods:  Effects of semi‐continuous MC compared to control plate culture (PC) and serial bead‐to‐bead transfer MC (MC bead‐T) on human BMMSCs were investigated. Cell population growth kinetics, cell phenotypes and differentiation potential of cells were assayed. Results:  Maximum cell density and overall fold increase in cell population growth were similar between PCs and MCs with similar starting conditions, but lag period of BMMSC growth differed substantially between the two; moreover, MC cells exhibited reduced granularity and higher CXCR4 expression. Differentiation of BMMSCs into osteogenic and adipogenic lineages was enhanced after 3 days in MC. However, MC bead‐T resulted in changes in cell granularity and lower osteogenic and adipogenic differentiation potential. Conclusions:  In comparison to PC, MC supported expansion of BMMSCs in an up‐scalable three‐dimensional culture system using a semi‐continuous process, increasing potential for stem cell homing ability and osteogenic and adipogenic differentiation.